Is there an optimal decision to delivery interval (DDI) for instrumental deliveries?. (7th June 2011) - Tower, C L; Wang, S J; Vause, S
Abstract : Background: We previously reported that the longer decision to delivery interval (DDI) associated with instrumental delivery in theatre was associated with a lower fetal cord pH. We therefore hypothesized that there is an optimal DDI for instrumental delivery that could be used as an audit standard. Methods: All instrumental deliveries from October 2008 to September 2010 in a tertiary referral centre were studied. Data were collected prospectively using an audit proforma that also served as medical documentation. Results: After exclusion of deliveries with absent or apparently erroneous DDIs, 1102 deliveries were analysed. 643 (58.3%) deliveries were conducted in the room. In this group, a DDI ≥8 min was associated with lower fetal cord pHs: mean arterial pH 7.12, ± 0.91 n=373, mean venous pH 7.12±1.36 n=418, p≤0.05 versus arterial cord pH 7.22, ± 0.08 n=59, venous cord pH, pH 7.28 ± 0.08 n=63. There were no differences when only deliveries conducted for abnormal CTGs were analysed. For deliveries in theatre (n=459) there were no differences comparing DDIs <30 min or <75 min. Conclusion: A shorter DDI for deliveries in the room was associated with better fetal cord pHs, suggesting that it may be possible to establish an audit standard. The lack of association with abnormal cardiotocography may highlight the difficulties in assessing the fetal wellbeing in the second stage. No differences were seen for deliveries in theatre using the same standards as for caesarean section, suggesting that providing evidence for theatre deliveries may be more challenging.